Swindle / 1. - Korman, Gordon (Korman, Gordon. Swindle mystery, 2008)
After unscrupulous collector S. Wendell Palamino cons him out of a valuable baseball card, sixth-grader Griffin Bing puts together a band of misfits to break into Palomino's heavily guarded store and steal the card back, planning to use the money to finance his father's failing invention, the Smart Pick fruit picker.